Civil Society and the Role of Schools, Citizenship Education, Pancasila and Religious Studies in Building Unity in Diversity - Choirul Mahfud; Ratna Rintaningrum; Niken Prasetyawati; Dyah S.Y Agustin; Ni Wayan Suarmini; Rahmawati Rahmawati; Rika Astari; Abdurrohman Kasdi (MODELING: Jurnal Program Studi PGMI, 2023)
Indonesia is a country that is united in diversity. It is reflected in the motto Bhinneka Tunggal Ika, Pancasila, and the 1945 Constitution. This research aims to determine the role of schools, civics education, Pancasila, and the views of religions and religious communities in Indonesia in realizing civil society. From the results of this study, it was found that the high level of diversity in Indonesia had occurred long ago and has continued until now and in the future. In this case, schools have a significant role in developing unity in diversity. Also, civic education, Pancasila, and religion have a role in unity in diversity in Indonesia.